The Effect Of The Ts-Ts Learning Model To Improve Speaking Skill At Grade X In SMA Negeri 1 Baktiraja - Nanda Claudia Sitorus; Christina Saragi; Harpen H.P. Silitonga; Rina Octavia Simarmata (Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this study is to help students improve their ability to speak an essay in the descriptive text genre. Descriptive text is a genre that uses spoken language to explain something to the reader. To make it easier for researchers to conduct research, a quasi-experimental approach is used. This method allows the researcher to get closer to the sample. For this study, the researcher chose two classes as samples. The sample in this study consisted of 72 students from SMA Negeri 1 Baktiraja. Quantitative data is an instrument for gathering information. After reviewing the data, researchers found differences between the experimental and control class. The average value of the data presented, calculated by SPSS version 25, shows that the score of the experimental class increased from 44.22 in the pre-test to 78.56 in the post-test as a result of learning the TS-TS, models treatment. The pre-test for the control class was 43.56, and the post-test was 50.56 because the researchers did not treat them. The average value of the control class pretest was 43.56. The t-test calculated from the post-test findings between the experimental and control groups was 53,949. The t-test result is more than 0.05 in this case. From the data presented, it can be concluded that there was an effect of using TS-TS learning model on students’ speaking skill in tenth grade students of SMA Negeri 1 Baktiraja in the academic year 2022/2023.